2015
DOI: 10.4088/jcp.14m09127
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Factors and Serotonin Transporter Gene Variants Associated With Antidepressant-Induced Mania

Abstract: Narrowly defined, AIM appears to be at greatest risk for bipolar I patients. Our haplotype analysis of SLC6A4 suggests that future pharmacogenetic studies should not only focus on the SLC6A4 promotor variation but also investigate the role of other variants in the gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 0 publications
1
33
2
Order By: Relevance
“…The AIM literature is complicated by differences in study populations and use of mood stabilizers, and most studies did not genotype rs25531. Despite these issues, a meta‐analysis of existing studies in patients on antidepressants (not exclusively SSRIs) shows a suggestive association of the S allele with AIM (p=0.059) . The observed association between gastrointestinal adverse effects and the S allele is not statistically significant in many individual studies but is fairly consistent in both Asian and white populations.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The AIM literature is complicated by differences in study populations and use of mood stabilizers, and most studies did not genotype rs25531. Despite these issues, a meta‐analysis of existing studies in patients on antidepressants (not exclusively SSRIs) shows a suggestive association of the S allele with AIM (p=0.059) . The observed association between gastrointestinal adverse effects and the S allele is not statistically significant in many individual studies but is fairly consistent in both Asian and white populations.…”
Section: Resultsmentioning
confidence: 97%
“…Of seven studies investigating 5‐HTTLPR in relation to AIM, three found significant evidence associating the S allele with increased odds of AIM, one showed a nonsignificant trend in that direction, and three showed little signal of association . Studies examining STin2 are consistent in that all three studies failed to show an association between STin2 and AIM . One group performed a haplotype analysis of 5‐HTTLPR, rs25531, and STin2 and concluded that the L A ‐10 haplotype is associated with a reduced risk of AIM – a finding that is physiologically confusing given the increased expression owed to the 5‐HTTLPR and rs25531 genotypes and decreased expression related to STin2 10 repeat allele.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our regression analyses showed that low‐expressing genotypes, those with an S allele, predicted child fear, but none of the genotypes predicted child AL. Historically, the 5‐HTTLPR gene and the rs‐25531 polymorphism have been associated with depression, obsessive compulsive disorder, and many psychiatric diagnoses, although many of these conflict in the nature of how the SNP regulates or affects these outcomes (Frye et al., ; Klauke et al., ; Voyiaziakis et al., ). Therefore, due to the inconsistent nature of both the literature and our findings, there is a need for further research examining child temperament and the 5‐HTTLPR polymorphism.…”
Section: Discussionmentioning
confidence: 99%